The causal-noncausal alternation in the Northern Tungusic languages of Russia - Natalia Aralova; Brigitte Pakendorf (Language Science Press, 2022)
Languages differ widely in the way they code causal-noncausal alternations, in which a verb event is either presented as happening by itself (the noncausal event) or as being instigated by an external causer (the causal event). Some languages, such as English, tend not to make a morphological distinction; rather, the same form of certain verbs can express both a causal and a noncausal event, depending on the context. Other languages, such as Romanian or Russian, have a strong tendency to mark the noncausal event morphologically, while yet others, such as Turkish, tend to code the causal event with morphological means (Haspelmath 1993). We here investigate the causal-noncausal alternation in Even, Negidal, and Evenki, three Northern Tungusic languages spoken in the Russian Federation, in a cross-linguistic perspective. In these languages, morphological means for decreasing and increasing valency predominate, although equipollence – in which both forms are morphologically marked without one being derivable from the other – is a salient strategy for verbs of destruction. Although we find broadly comparable coding patterns in these and other Tungusic languages that are similar to what is found in other languages of Northern Asia, there are numerous intriguing differences at a fine-grained level.